Primary school students' knowledge about animal life cycle material: The survey study - Nasir, Nur Indah Ririn Fitriani; Mahanal, Susriyati; Ekawati, Ratna; Damopolii, Insar; Supriyono, Supriyono; Rahayuningsih, Sri (Univeritas Papua, 2024)
Students' knowledge is obtained from studying, and their involvement in science learning is still low, so it is a concern. Our research aims: First, to survey students' knowledge of animal life cycles, and second, to determine differences in students' knowledge of animal life cycles based on gender. This research uses a survey method. Sampling was carried out using convenience sampling. The sample obtained was 286 students willing to answer questions via Google Forms. They are primary school students in Indonesia. Data collection procedure: (1) compiling the instruments, (2) expert validation, (3) instrument testing, (4) validity and reliability analysis, (3) test distribution, (4) analysis of findings, (5) data interpretation, and (6) conclusion. A total of 9 valid and reliable questions were used to collect data. Analysis of differences in student knowledge using the Mann-Whitney test. The findings show that there are still 51.75% of students whose knowledge needs to be improved. Boys and girls students did not show differences in their knowledge regarding animal life cycles. This research concludes that students' knowledge of animal life cycle material has not reached the good category. Boys and girls students have the same level of knowledge but only get the moderate category. Future research can test how innovative learning in science for primary schools can impact student knowledge.